Perceptions of factors affecting growth in the Small-Scale Embedded Solar Photovoltaic sector in South Africa - Hlebela, Meddas Charles (My University, 2022)
South Africa is experiencing electricity shortages due to the various challenges faced by Eskom. This has resulted in Eskom implementing rotational power cuts, commonly known as ‘load shedding’. Small-scale embedded solar photovoltaic systems are ideal in offering immediate solutions to address the current power shortages and to ensure the country’s security of electricity supply. The study utilised the socio-technical transition framework to investigate the perceptions of factors affecting growth in the small-scale embedded solar PV sector in South Africa. The study utilised a qualitative research approach. A total of thirteen (13) interviews were conducted, using a semi-structured interview guide. Purposive sampling, which is sometimes called selective sampling, was utilised for this study. The respondents for this study consisted of stakeholders with significant knowledge, expertise, and interest in the energy industry which included policy, regulation, commercial banks, utilities, financial, energy experts, as well as energy journalists and energy analysts. The findings indicate that socio-technical factors which include institutional, technical, economic, and social factors affect growth of the small-scale embedded solar PV sector in South Africa both positively and negatively. The findings identified the key challenges facing the sector to include lack of funding, regulatory burden, unattractive feed-in tariffs and lack of a clear regulatory framework. The key recommendations of this study include the development of active strategy from government and the regulator to promote the small-scale embedded solar PV sector, the need for shortening or streamlining of the regulatory processes to facilitate establishment of more small scale embedded generations in the country, introduction incentives such as feed-in tariffs and tax incentives, as well as increasing the threshold of small scale embedded generators of more than 1MW to only register and not need a generation licence. The findings confirm that socio-technical factors of institutional, technical, economic, and social factors affect growth of the sector. The growth of the sector is critical and is urgently required to address the electricity supply challenges in South Africa.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in the field of Energy Leadership
Keywords: Embedded generation; Factors affecting growth; Perceptions; Small-scale; Embedded; Generation; Solar Photovoltaic; SDG-8: Decent work and economic growth